2022
DOI: 10.1021/acs.est.2c01707
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Electrochemically Accessible Sites in Flow-through Mode for Maximizing Available Active Area toward Superior Electrocatalytic Ammonia Oxidation

Abstract: Active chlorine species-mediated electrocatalytic oxidation is a promising strategy for ammonia removal in decentralized wastewater treatment. Flow-through electrodes (FTEs) provide an ideal platform for this strategy because of enhanced mass transport and sufficient electrochemically accessible sites. However, limited insight into spatial distribution of electrochemically accessible sites within FTEs inhibits the improvement of reactor efficiency and the reduction of FTE costs. Herein, a microfluidic-based el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that the reactions between FC and Cl • also contribute to the formation of ClO • (eqs and ). , Its high reactivity and selectivity toward ammonium oxidation to nitrogen even at acidic pH values is noteworthy (eq ). ,, Small amounts of nitrate resulting from HClO-mediated ammonium oxidation (eq ) are directed to the cathode via internal recycling and expected to be reduced by the electrons and/or adsorbed H (H*) from the cathode (eqs and ). , H 2 O H + + OH OH + MO x ≡MO x false( normalHO false) + e Cl + ≡MO x false( normalHO false) Cl + OH + MO x …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the reactions between FC and Cl • also contribute to the formation of ClO • (eqs and ). , Its high reactivity and selectivity toward ammonium oxidation to nitrogen even at acidic pH values is noteworthy (eq ). ,, Small amounts of nitrate resulting from HClO-mediated ammonium oxidation (eq ) are directed to the cathode via internal recycling and expected to be reduced by the electrons and/or adsorbed H (H*) from the cathode (eqs and ). , H 2 O H + + OH OH + MO x ≡MO x false( normalHO false) + e Cl + ≡MO x false( normalHO false) Cl + OH + MO x …”
Section: Resultsmentioning
confidence: 99%
“…29,53 Its high reactivity and selectivity toward ammonium oxidation to nitrogen even at acidic pH values is noteworthy (eq 13). 16,26,28 Small amounts of nitrate resulting from HClOmediated ammonium oxidation (eq 14) 11 are directed to the cathode via internal recycling and expected to be reduced by the electrons and/or adsorbed H (H*) from the cathode (eqs 15 and 16). 54,55 H O H OH…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…However, flaky Ru/HMCs-1000 are different from the other spherical Ru/HMCs- x , because this structure is not beneficial for the transport of substances and the diffusion of reactants. The HER becomes the mass transfer limitation at large polarizations, 42 so the activity is affected by the volumetrically averaged mass transfer coefficient. Therefore, the current density in the LSV polarization curve of Ru/HMCs-1000 is lower than that of Ru/HMCs-500 although Ru/HMCs-1000 have a larger electrochemically accessible surface.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical oxidation is a very promising technology for ammonia wastewater treatment, but it also has the prominent disadvantage of high energy consumption. , In recent years, many studies have been conducted to solve this problem, including research on a catalytic electrode with high efficiency, , enhancement of the reaction kinetic process, and optimization of experimental conditions. , However, enhancing the recovery of H 2 via the exploitation of electron acceptors at the cathode is often overlooked, which is meaningful to reduce the energy consumption but increase the wastewater resource utilization. Hence, an advanced electrochemical reactor with simultaneous hydrogen recovery and ammonia remains a vital problem for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%